Risk map of human intake of mercury through fish consumption in Latin America and the Caribbean - Vergara, Elvira; Pancetti, Floria; Zúñiga, Liliana; Fabres, Karen; Bahamonde, Paulina (Frontiers in Sustainable Food Systems, 2024)
Mercury (Hg) is a persistent pollutant highly bioaccumulated in the aquatic environment through the food chain reaching high concentration levels in the tissues of predator fishes. Among the relevant sources of anthropogenic mercury emissions in Latin America and the Caribbean (LAC), mining is one of the most important along with soil erosion due to deforestation and agricultural activities where pesticides are intensively used. Several reports have demonstrated an association between a fish-based diet with elevated Hg levels in the blood and neurotoxic effects in humans. In this systematic review with quantitative analysis data from 92 articles were compiled, providing evidence of Hg concentration in fishes that are commonly consumed in LAC. An assessment was conducted using three indices for health risk: the Minamata Initial Assessment (MIA), the Target Hazard Quotient (THQ), and the Meals per Week (MPW) index. Of the 410 fish species studied, 5.4% had concentrations above 0.95 μg g−1 of wet weight (ww), which is the recommended limit for Total Hg (THg) ingestion through fish consumption according to the MIA index, regardless of the water habitat (i.e., marine or freshwater). Additionally, the Target Hazard Quotient (THQ) calculation indicated high-risk values (THQ ≥ 1) in 15 out of the 19 countries studied, and very high-risk values (THQ ≥ 10) were obtained from Hg concentrations measured in 5 fish species inhabiting watersheds in Trinidad and Tobago, Suriname and Peru. Finally, recommendations on fish consumption were made based on the MPW index. This study reveals the need for updated biomonitoring studies of Hg concentrations in fish to perform more accurate human health risk analyses.